Toward mitigating pressure injuries: Detecting patient orientation from vertical bed reaction forces. (March 2020) - Wong, Gordon; Gabison, Sharon; Dolatabadi, Elham; Evans, Gary; Kajaks, Tara; Holliday, Pamela; Alshaer, Hisham; Fernie, Geoff; Dutta, Tilak
Introduction: Prolonged bed rest without repositioning can lead to pressure injuries. However, it can be challenging for caregivers and patients to adhere to repositioning schedules. A device that alerts caregivers when a patient has remained in the same orientation for too long may reduce the incidence and/or severity of pressure injuries. This paper proposes a method to detect a person's orientation in bed using data from load cells placed under the legs of a hospital grade bed. Methods: Twenty able-bodied individuals were positioned into one of three orientations (supine, left side-lying, or right side-lying) either with no support, a pillow, or a wedge, and the head of the bed either raised or lowered. Breathing pattern characteristics extracted from force data were used to train two machine learning classification systems (Logistic Regression and Feed Forward Neural Network) and then evaluate for their ability to identify each participant's orientation using a leave-one-participant-out cross-validation. Results: The Feed Forward Neural Network yielded the highest orientation prediction accuracy at 94.2%. Conclusions: The high accuracy of this non-invasive system's ability to a participant's position in bed shows potential for this algorithm to be useful in developing a pressure injury prevention tool.